Consideration of education as a public service in spanish legislation - Galicia Mangas, Francisco Javier (Avances en Supervisión Educativa, 2020)
After a brief introduction in which some of the difficulties in integrating education into the complex category of public services are referred to, this study attempts to make a brief reference to the concept of public service, its evolution, and its application to the educational field. Secondly, a quick study of the principle of subsidiarity is made to recall, with jurisprudential support, that our current system is not based on the struggle between public and private, but rather that the educational service is provided by three types of centres: public schools, private schools and subsidized private schools. The main or central block of the work deals, in an outstanding way, with the study of education as a public service in Spanish legislation, starting from the Law of Public Instruction of 1857 and the General Law of Education of 1970, to arrive, with help of doctrinal approaches, to laws subsequent to the CE of 1978, and especially to the provisions in this regard in the LODE, the LOCE and the current LOE, modified by LOMCE. Finally, a brief reference is made to some exceptional circumstances that surrounded the exercise of the right to education in the times of pandemic that we live today. Finally, a brief reference is made to some exceptional circumstances surrounding the exercise of the right to education in the times of pandemic that we live in today.